Pengaruh Model Kooperatif Think Pair Share (Tps) Terhadap Hasil Belajar Passing Bawah Dalam Bola Voli Kelas Viii Smp N 1 Japah Tahun Ajaran 2019/2020 - Agus Setiawan (YLPK Mahardhika, 2021)
The motivation for this research is the lack of optimal learning by teachers and the lack of value for students in learning volleyball. Many students are passive when learning activities occur. The purpose of this research is to use the Think Pair Share cooperative learning method in SMP N 1 Japah to determine the progress of students' learning outcomes in Class VIII. The results of showed that before the study of the Think Pair Share method, the average learning outcome increased to 64, and after the study of the Think Pair Share learning model, it increased to 70. Therefore, the increase of 6 The type of research is quantitative research. In this study, the researchers used a pre- and post-test design. The advice given by the researchers is that teachers should optimize learning. Students are more active in the learning process.